2015
DOI: 10.3171/2015.5.focus15164
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following myxopapillary ependymoma resection: the importance of capsule integrity

Abstract: OBJECT While extent of resection has been shown to correlate with outcomes after myxopapillary ependymoma (MPE) resection, the effect of capsular violation has not been well studied. The role of adjuvant radiation also remains controversial. In this paper the authors' goals were to evaluate outcomes following resection of MPE based on intraoperative capsular violation and to explore the role of adjuvant radiotherapy in cases of capsular violation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 24 publications
1
43
2
Order By: Relevance
“…Multiple previous reports have investigated outcomes based on extent of surgical resection. It is a near universal finding that GTR improves outcomes, often measured as progression-free survival (PFS); while not statistically significant in this cohort there was a trend towards improvement in OS in patients receiving GTR in this analysis [6][7][8][9][10][11][12][13][14]. The few mean tumor size among those receiving RT (4.6 cm) was significantly larger than among those not receiving RT (3.2 cm, p = 0.0002).…”
Section: Discussioncontrasting
confidence: 50%
“…Multiple previous reports have investigated outcomes based on extent of surgical resection. It is a near universal finding that GTR improves outcomes, often measured as progression-free survival (PFS); while not statistically significant in this cohort there was a trend towards improvement in OS in patients receiving GTR in this analysis [6][7][8][9][10][11][12][13][14]. The few mean tumor size among those receiving RT (4.6 cm) was significantly larger than among those not receiving RT (3.2 cm, p = 0.0002).…”
Section: Discussioncontrasting
confidence: 50%
“…In cases of MPE, it is important to consider whether maximal resection is worth the potential risk of injury, since evidence of a benefit with GTR is currently lacking for these tumors. Some researchers have suggested that preservation of capsular integrity may be important for preventing recurrence of MPE, however, definitive evidence is currently lacking [34, 35]. Further research is required to define the optimal surgical techniques for preservation of neurologic function and prevention of later recurrence.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…22,23 If possible, en bloc resection is preferable to piecemeal resection, as tumor capsule NeuroOncology Neuro-Oncology Practice violation has been reported to increase the risk of CSF seeding and metastasis, while GTR without tumor capsule violation may be curative. 19,24 Despite its extramedullary location and benign grade, MPE carries a long-term prognosis similar to that of WHO grade II ependymoma, perhaps because of a lower overall GTR rate. 25 Oh et al reported in their meta-analysis no difference in OS or PFS between MPE and grade II ependymoma.…”
Section: Intramedullary Spinal Cord Ependymomamentioning
confidence: 99%